Effectiveness of Activity Based Costing Implementation in Service Business Pricing Decision - Nia Sahara Basyar (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research aims to analyze the effectiveness of implementing the Activity Based Costing (ABC) method in calculating the Cost of Good Sold (COGS) and Cost of Revenue (COR), and its impact on product pricing decisions in Q-Buket Pematangsiantar, a creative service business specializing in bouquet making. Traditionally, the business has used the Cost Plus Pricing method, which only considers direct material costs with a fixed markup, without accounting for actual activities involved in service delivery. Through a case study of five bouquet types (flower, money, snack, doll, and mixed), the findings show that the ABC method enables more accurate cost allocation based on real consumption of activities such as customer communication, decoration, packaging, and delivery. The resulting product prices are more proportional to each product’s complexity compared to those calculated using the previous method. Therefore, Activity based costing proves to be more effective in improving cost accuracy, operational efficiency, and strategic pricing decisions. It is recommended for service-based creative businesses that involve diverse and value-adding processes.